The role of leadership in developing a strong employer brand. (8th October 2020) - Jain, Sonal
Organisations today have their task cut out in the form of attracting talented employees, engaging them and retaining them in the process. Through this study, the researcher studied the construct of employer branding and appropriated the various factors which constitute employer branding. Further, the study also made an important contribution by linking the role of leadership in the development of a strong employer brand of an organisation. This research extracted five important factors of employer branding, viz., organisational fit, perceived organisational reputation, leadership and transparency, strong management, and work atmosphere. Each factor contributes immensely to the construct of employer branding and the effective understanding of each one of them can be very useful for an organisation to create an impactful employer brand in the era of start-ups, social media revolution and internet communication.